Synthesis and Characterizations of Mullite Based Glass–Ceramics from Agricultural Wastes - Jain A.; Kushwaha R.; Sharma A.; Rajotia M.; Saroj V.K.; Panda S. (My University, 2025)
This study mainly focuses on using agricultural wastes in useful engineering products. Rice husk and coconut husk were successfully used to produce mullite (3Al2O3-2SiO2) based glass–ceramics using a well-known vitrification/devitrification technique. The as-received wastes were washed, dried, and combusted at high temperatures to obtain the corresponding ashes. Two glass batches (GC1 and GC3) were prepared by proportioning the ashes, soda ash, and alumina. The GC3 sample has been completely vitrified at 1500 °C, whereas the GC1 sample with a higher percentage of silica (>90%) could not produce glass at the identical heat treatment schedule. The controlled nucleation-crystallization of the GC3 glass at a single temperature of 1250 °C has led to mullite-based glass–ceramics. The DSC analysis of the GC3 glass sample identified the crystallization temperature. The XRD, SEM, and FTIR studies characterized and analyzed the mullite phase. In addition, the dielectric properties of the GC3 glass–ceramic are found to be suitable for radome materials. Thus, the obtained mullite based glass–ceramics are promising for structural, optoelectronics, and other high temperature applications. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.